ANALISIS KINERJA EFISIENSI KELEMBAGAAN RANTAI PASOK KLASTER UKM KERIPIK KENTANG MENGGUNAKAN PENDEKATAN DATA ENVELOPMENT ANALYSIS - Siti Asmaul Mustaniroh; Riska Septifani; Sri Wahyu Pangesti (Jurnal Teknologi Industri Pertanian, 2023)
Cluster of potato chips is the one of SMEs groups which growing up in Batu City. The existing conditions in 2020-2021 caused some problem for the clusters it is a decreasing in demand, marketing, and business performance due to impact from pandemic which causes an imbalance in the number of sales with the production produced. In the first trimester of 2022, demand product of potato chips has increased so the efficient performance for production process is needed to recovery. The efforts to restore a business performance can be done by increasing efficiency in the supply chain institutional system. The purpose of research is analyze performance value, find out input sub-variables who most influence, and propose improvement strategies in clusters of potato chips. This research used Data Envelopment Analysis CCR-I Dual models with input sub-variables consist of cash to cash cycle time, lead time, flexibility, and cost. Sub-variable output consist of percentage compliance with quality standards, order fulfillment, delivery performance,and revenue. This analysis was carried out on SMEs to retailers with Decision Making Unit (DMU) the result showed that DMU 2, DMU 3, DMU 5, DMU 6, and DMU 7 were in efficient condition meanwhile 4 DMUs are inefficient condition. Input sub-variable can impact performance efficiency is cost of supply chain. To increase performance value, DMU in clusters of potato chips must be minimizing input variables, improving of production planning, sales forecasting, and strategy innovation in marketing to increase sales and product competitiveness. Keywords: data envelopment analysis, efficiency; supply chain performanc, potato chips cluster